Exercise training in chronic heart failure. (May 2013) - De Maeyer, Catherine; Beckers, Paul; Vrints, Christiaan J.; Conraads, Viviane M.
The syndrome of heart failure (HF) is a growing epidemic that causes a significant socio-economic burden. Despite considerable progress in the management of patients with HF, mortality and morbidity remain a major healthcare concern and frequent hospital admissions jeopardize daily life and social activities. Exercise training is an important adjunct nonpharmacological treatment modality for patients with HF that has proven positive effects on mortality, morbidity, exercise capacity and quality of life. Different training modalities are available to target the problems with which HF patients are faced. It is essential to tailor the prescribed exercise regimen, so that both efficiency and safety are guaranteed. Electrical implanted devices and mechanical support should not exclude patients from exercise training; however, particular precautions and a specialized approach are advised. At least 50% of patients with HF, older than 65 years of age, present with HF with preserved ejection fraction (HFPEF). Although the study populations included in studies evaluating the effect of exercise training in this population are small, the results are promising and seem to support the idea that exercise training is beneficial for HFPEF patients. Both the short- and especially long-term adherence to exercise training remain a major challenge that can only be tackled by a multidisciplinary approach. Efforts should be directed towards closing the gap between recommendations and the actual implementation of training programmes.